CRITERIA, INDICATORS, LEVELS AND DIAGNOSTICS METHODS OF DEVELOPMENT OF PHYSICAL EDUCATION TEACHERS’ PEDAGOGICAL COMPETENCE IN AGRARIAN UNIVERSITY - Petrenko, Natalya (Continuing Professional Education: Theory and Practice, 2020)
This article defines the criteria for the formation of the pedagogical competence of scientific and pedagogical workers in physical education (motivational-value, cognitive-processual, developmental, educational, health-saving, communicative), their structure, content and measurement methods are disclosed. The determination of the components of the pedagogical competence of scientific and pedagogical workers of physical education makes it possible to significantly expand the range of pedagogical knowledge, skills and abilities of scientific and pedagogical workers of physical education, as well as to carry out their diagnostics as a kind of reference point for the content of the methodological work of the model of the educational process, which will help to adjust the process of development of pedagogical competence scientific and pedagogical workers of physical education in the methodological work of an agricultural university. The interrelation of components of pedagogical competence of physical education teachers of agrarian university with normative requirements to the organization of educational process on physical education and mass sports in institutions of higher education is established, (motor activity, individual work and practical classes) as well as with the tasks of agrarian education (maintaining the health of students, ensuring the health of the population through professional activities, solving environmental problems). For self-improvement of scientific and pedagogical workers of physical education the selection and modification of methods was carried out. To assess the development of pedagogical competence in the system of methodical work of the university, a system of tests was developed to determine the formation of each component.